Enhanced waste activated sludge dewaterability by tannic acid conditioning: Efficacy, process parameters, role and mechanism studies. (20th December 2019) - Ge, Dongdong; Zhang, Wenrui; Yuan, Haiping; Zhu, Nanwen
Abstract: Extracellular polymeric substances (EPS), especially proteins, exert a vital role in sludge dewatering. Tannic acid (TA), a plant secondary metabolite, is capable of bonding with proteins, and herein we employed it as a novel conditioner for sludge dewatering. The results indicated that TA enhanced sludge dewaterability with high reductions of 81.3% capillary suction time, 87.5% specific resistance of filtration and 13.4% water content of dewatered sludge under the optimized process parameters: TA dosage of 0.15 mmol/gTS, stirring speed of 200 r/min for 1 min, and settling time of 15 min. TA altered sludge properties pronouncedly including viscosity, particle size, zeta potential, pH and EPS contents and correlation analysis revealed their associations with sludge dewaterability. Moreover, EPS fluorescent components, sludge functional groups and surface morphology were detected for a better understanding of TA conditioning mechanism. The findings provide not only the feasibility of TA but also the potential of TA-containing plant waste in sludge treatment. Graphical abstract: Image 1 Highlights: TA enhanced WAS dewaterability efficiently with optimized process parameters. Sludge properties altered pronouncedly especially EPS proteins in TA conditioning. High efficacy of TA on complexing, bridging and precipitating sludge aggregates.